2008
DOI: 10.1049/el:20081842
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop linear dispersion coded eigen-beam transmission and its capacity

Abstract: A flexible closed-loop multiple-input-multiple-output (MIMO) system amalgamating linear dispersion codes and eigen-beam transmission is proposed that achieves a higher capacity than the equivalent openloop scheme, at the cost of feeding back a modest number of feedback bits from the mobile to the base station using Grassmannian beamforming-vector quantisation.Introduction: The single-stream eigen-beam transmission scheme of [1] achieves significant array gains over open-loop schemes in multipleinput-multiple-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recent researches have extended the space-time coding selection (i.e. codebook based precoding) into the LDC framework [27]- [32]. An important result was obtained in [29], where it is shown that f b =log 2 (M) feedback bits are enough to achieve full diversity.…”
Section: Advanced Transmission Techniques In Wimax 114mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent researches have extended the space-time coding selection (i.e. codebook based precoding) into the LDC framework [27]- [32]. An important result was obtained in [29], where it is shown that f b =log 2 (M) feedback bits are enough to achieve full diversity.…”
Section: Advanced Transmission Techniques In Wimax 114mentioning
confidence: 99%
“…An important result was obtained in [29], where it is shown that f b =log 2 (M) feedback bits are enough to achieve full diversity. In [32], the authors showed that the average SNR can be improved up to 2dB compared to the open loop scheme with only 3 feedback bits (i.e. 8 sets of LDC codes).…”
Section: Advanced Transmission Techniques In Wimax 114mentioning
confidence: 99%
“…Recent researches have extended the space-time coding selection (i.e. codebook based precoding) into the LDC framework [27]- [32]. An important result was obtained in [29], where it is shown that f b =log 2 (M) feedback bits are enough to achieve full diversity.…”
Section: Mimo Precoding Based On Ldc Codesmentioning
confidence: 99%
“…An important result was obtained in [29], where it is shown that f b =log 2 (M) feedback bits are enough to achieve full diversity. In [32], the authors showed that the average SNR can be improved up to 2dB compared to the open loop scheme with only 3 feedback bits (i.e. 8 sets of LDC codes).…”
Section: Mimo Precoding Based On Ldc Codesmentioning
confidence: 99%